Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Given the base function y= log2(base)X. Rewrite y = log2(base) square root of X over 4 as the transformation of the base function.

Given The Base Function Y Log2baseX Rewrite Y Log2base Square Root Of X Over 4 As The Transformation Of The Base Function class=

Sagot :

Answer:[tex]\begin{gathered} y=2\log _2x-2 \\ \text{where }\log _2x\text{ is the base function} \end{gathered}[/tex]Explanation:

Let the base function be:

[tex]f(x)=\log _2x[/tex]

The second function is:

[tex]y=\log _2\frac{\sqrt[]{x}}{4}[/tex]

This can be re-written as:

[tex]\begin{gathered} y=\log _2\sqrt[]{x}-\log _24 \\ y=\log ^{}_2x^2-\log _22^2 \\ y=2\log _2x-2\log _22 \end{gathered}[/tex]

Note that:

[tex]\begin{gathered} \log _22=1 \\ \end{gathered}[/tex]

The resulting transformed expression therefore becomes:

[tex]\begin{gathered} y=2\log _2x-2(1) \\ y=2\log _2x-2 \end{gathered}[/tex]